Language and the world represented in Phelipe Guaman Poma de Ayala's work - Labastida, Jaime (2013)
The cosmos described by Guaman Poma is, on the one hand, similar to that found in the biblical Genesis, and on the other hand, to the one in the Myth of the five Suns of the culture nahuatl. Guaman Poma is a Ladino or Latin Indian, who writes in 16th-century Spanish. From an ethnic angle, he is a pure Quechuan, but from the cultural angle, he is a Westernized Quechuan. Hispanicized and hybrid, Phelipe Guaman (Falcon) Poma (Cougar, American Lion) de Ayala has a good command of Spanish. His book is a hybrid or mestizo Codex: on the odd pages there is always a drawing which shows influence of the Western perspective; on the even pages, a text talks about the drawings. Each written page translates or talks about the drawing. Just as, in view of the Codex nahuatl, the verbal torrent of the tlamatini (priest or wise Aztec who recites what is “written” in the painting) unleashes, the drawings of Guaman Poma trigger the memory of that who writes them. These stories have life: they have the same function of the Inca quipus and codices: to unleash the wise’s torrent of words, which recalls the sacred anthem. Nueva coronica i buen gobierno (The First New Chronicle and Good Government) starts after the letter to his Majesty, Felipe III; and the preface begins with the story of the creation of the world. At that point follows the sequence of the biblical Genesis and is based on the Old and New Testament. If it were limited to the servile repetition of the Bible, the story of Guaman Poma would lack of interest; but it is not so. From the very first pages there is something unusual in the text of the Inca chronicler. Guaman Poma interprets the creation found in Genesis (the creation of the world and the creation of man) by means of a syncretism with specific categories or mental structures of the Quechuan culture from which it comes. Our presentation will seek to explain, precisely, the language and the world represented in the work of the chronicler, historian and mythologist Phelipe Guaman Poma de Ayala.